DIGITAL ECOSYSTEMS AS A CATALYST FOR ACADEMIC MOBILITY IN TRANSNATIONAL HIGHER EDUCATION - Yang Haifeng (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Academic mobility in transnational higher education faces traditional barriers including visa restrictions, high costs, and cultural adaptation challenges. This paper examines how digital ecosystems serve as catalysts for redefining academic exchange models through virtual mobility, digital credentials, and collaborative platforms. The study analyzes the application mechanisms of digital technologies in educational management, credit recognition, and international cooperation, proposing a framework for developing blended mobility models. The conclusion indicates that integrated digital ecosystems can effectively enhance the accessibility and quality of transnational education, providing strategic guidance for educational institutions.